A Study on the Customer Segmentation based on Psycho Graphics towards the Eco Label Awareness among the Indian Food and Grocery Retailing Customers - et. al., V. Sravani Chari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is emphasised to understand the psycho-graphic segmentation of online food and grocery retailing customers towards the eco label awareness. The study considered VALS (Values and life styles) model as the base for this paper. The better psychological understanding helps the marketers to served them in a better way. Hence, the data has been collected from the Indian customers who preferred online to purchase their food and grocery products. There are 117 samples drawn for this study and applied cross-tabulation analysis. The results of the study are provided elaborately in the paper